Analisis Penerapan Akuntansi Murabahah Berdasarkan PSAK 102 (Studi Kasus BMT Maslahah Cabang Pembantu Diwek) - Luluk Ernawati (JFAS : Journal of Finance and Accounting Studies, 2020)
The purpose of this research is to know appropriateness of a murabahah accounting related to the recognition, measurement, performance and disclosure at BMT Maslahah Capem Diwek in order to improve professionalism and public trust that the implementation of a Murabahah transaction already fit with the accounting standards. This research uses qualitative descriptive method by describing and comparing data obtained by researchers directly regarding the recognition, measurement, performance and disclosure of Murabahah transactions. Research Data obtained by researchers through observations, interviews and documentation with the head of office, accounts of financing officers and the teller section of the BMT Maslahah Capem Diwek. The results of this research show that the practice of Murabahah accounting in transaction financing related to the recognition, measurement, performance and disclosure of transactions accounting Murabahah at BMT Maslahah Capem Diwek is not in accordance with PSAK 102.